Offensive performance indicators in a regular season of water-polo - Ordonez, E. G.; Gonzalez, C. T.; Perez, M. del C. I. (International Journal of Performance Analysis in Sport, 2015)
The purpose of the present study was to identify offensive performance indicators that may discriminate by match score (favourable, balanced or unfavourable). The sample comprised 88 regular season games (2011-2014) from the Spanish Professional Water-Polo League. Univariate (ANOVA test; Kruskal-Wallis test and Generalized Linear Model test (GLM)) and multivariate (Discriminant) analysis to compare favourable, balanced or unfavourable and confidence intervals and effect sizes of the differences were calculated. The results showed that favourable games had averages that were significantly higher for counterattack attacks